Analisis Pengetahuan tentang Donor Darah untuk Kesehatan Kepada Masyarakat di PMI Kota Medan - Fauziah Azzuardini Ginting; Juredah Juredah; Miftahul Khairat; Usiono Usiono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The death rate due to the unavailability of blood reserves in developing countries is relatively high. In fact, the percentage of blood donors is still low which causes limitations in meeting the increasing demand for blood. This limited number of blood donors can be caused by lack of knowledge about blood donors, wrong assumptions or perceptions about blood donors, or fear of technical blood donation procedures. This study aims to describe knowledge about blood donation, and the importance of blood donation for health. This research uses a descriptive qualitative research approach, namely by using the interview method. The object of this research is 3 PMI members. The results of the study stated knowledge about blood donation, the importance of blood donation for health and the impact of blood donation. Keywords: Knowledge, Benefit, Impact.